Konflik Batin Tokoh “Aku” dalam Novel Garis Waktu Karya Fiersa Besari - Rumadi, Hadi; Syafrial; Fajriani, Sri Wulan (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
The inner conflict is a part of the prosaic objectivity elements that are inherent in the characters, especially novels. It occurs as the attraction of the story so that the values ​​of ethics and personal values ​​are illustrated that can be enjoyed. Internal conflict as a reflection of the fact of humanity that is always faced by anyone, does not rule out the possibility of figures contained in literary works. With its existence makes the story more alive and meaningful with all events in it. The focus of inner conflict in this novel is the perspective of the first person 'I', the author of the novel himself, Fiersa Besari. So, this study aimed to describe the inner conflict on the character